The Application of Islamic Business Ethics in Modern Markets: Principles, Challenges, and Opportunities in a Globalized Economy - Sikki, Nurhaeni; H, Rahma Indhytsania; Tumbas, Gradiana; Mayusip, Billy; Mamengko, Waraney; Dotulong, Dean Joshua (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This paper examines the principles, challenges, and opportunities associated with applying Islamic business ethics in contemporary markets, focusing on how Sharia-based ethical frameworks interact with the realities of globalized trade and digital transformation. Drawing on classical sources such as the Qur’an and Hadith, as well as modern interpretations from Islamic scholars, the study identifies core principles including justice (adl), trustworthiness (amanah), transparency (shafafiyah), prohibition of usury (riba), and avoidance of uncertainty (gharar). Using a qualitative approach based on literature review and case analysis, this paper finds that Islamic business ethics provide a holistic framework that fosters integrity, social responsibility, and sustainable growth. However, businesses face challenges such as navigating interest-based global financial systems, ensuring halal compliance in supply chains, and addressing ethical concerns in digital markets. Opportunities arise in the expanding halal industry, ethical finance, and the growing demand for value-based commerce among Muslim and non-Muslim consumers.